PENDAMPINGAN PEMBUATAN KEMASAN PADA USAHA GULA AREN DI DESA RAPPANG - Sappeami; Husain; Sapri; Irwandi; Baharuddin; Himawan, Ferdiansyah (LPPM ITB AAS Indonesia Surakarta, 2025)
Packaging is a crucial aspect that consumers consider when selecting a product to consume. Therefore, as an entrepreneur, it is essential to prioritize this aspect in business management. Based on a survey conducted, it was found that in Rapang Village, several people engage in the production of palm sugar, but none of the entrepreneurs have unique packaging. Hence, assistance was provided in packaging design, followed by socialization, with the aim of increasing product recognition within the community and attracting consumer interest in choosing the product for consumption. The method used in the assistance process involved direct support to entrepreneurs in determining the brand and label for the packaging. Furthermore, the assistance extended to the installation of a signboard in front of the house of one of the palm sugar entrepreneurs in Rapang Village, Tapango District.The results of this activity led to the creation of a new product with more attractive packaging than before. Additionally, this initiative had a positive impact by raising awareness about the importance of product packaging and motivating entrepreneurs to further develop their businesses.